Food Insecurity and Associated Demographic, Academic and Health Factors Among Undergraduate Students at a Large Urban University. (29th May 2020) - Ryan, Rachel; Murphy, Bridget; Deierlein, Andrea; Parekh, Niyati; Bihuniak, Jessica
Abstract: Objectives: The estimated prevalence of food insecurity among college students is approximately 41%. In response, colleges are implementing food support programs such as campus food pantries and free meals through campus cafeterias. However, there is limited research on prevalence estimates of food insecurity on campuses that have adopted support programs, and if food insecurity on such campuses is associated with known demographic risk factors and health behaviors. The purpose of this study was to assess food insecurity and associated demographics, grade point average (GPA) and health behaviors among undergraduate students attending a 4-year urban university that has a short-term food support program. Methods: Undergraduate students (≥18 years of age, NYU) were recruited via email to participate in a Qualtrics survey, which included: 1) the U.S. Household Food Security Survey Module (6-item short form), 2) the Pittsburgh Sleep Quality Index, 3) the Fruit & Vegetable Intake Screener in EATS, and 4) Beverage Questionnaire (BEVQ-15). Demographics, self-reported health status and GPA were assessed. Descriptives, t-tests, Mann-Whitney U, and chi-square analyses were conducted. Results: Two hundred and fifty-seven participants completed the survey (age = 20.1 ± 2.5; 82% female; 97.3% full-time). Forty-one % were food insecure. Food insecurity was significantly associated ( P  < 0.05) with race, ethnicity, health status and GPA. Students who identified as black/African American or Hispanic had an increased risk of food insecurity; conversely those who identified as Asian had a decreased risk. A greater percentage of food insecure students reported a GPA of <3.0 (67 vs. 42%) and fair/poor health (31 vs. 18%). Food insecurity was not associated with fruit/vegetable intake, sugar sweetened beverage consumption, or sleep quality, with the majority of students not meeting recommendations. Conclusions: Despite having an on-campus, food support program, our data suggests a high prevalence of food insecurity among students attending a large urban university. Food insecurity was associated with demographic risk-factors, lower GPA and fair/poor health status. For food support programs to be most effective, colleges should consider frequent evaluation of program awareness/accessibility. Funding Sources: The Institute of Human Development and Social Change.